Weight Gain in Type 2 Diabetes Mellitus Patients Receiving Sulfonylurea Medications at a Tertiary Hospital in Surabaya, Indonesia - Respati, Ghagat Dresta Putra; Prajitno, Jongky Hendro; Setiawati, Rosy; Wironegoro, Rio (Universitas Airlangga, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia. The prevalence of diabetes in Indonesia is 1.5%, although East Java recorded a 2.1% rate in 2013. T2DM medications, such as sulfonylureas, may lead to hypoglycemia and weight gain. This study aimed to investigate the weight gain effects of sulfonylureas in T2DM patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This retrospective cross-sectional study used retrograde anamnesis on 41 T2DM patients receiving sulfonylurea medications for the preceding six months. The data were collected from medical records and interviews with the T2DM patients who received treatment at the Internal Medicine Clinic of Dr. Soetomo General Academic Hospital from January to June 2022. Results: Most patients were 46–65 years old (73.2%), female (51.2%), and had been diabetic for over 15 years (48.8%). The predominant medications administered to the patients were glimepiride (41.4%) and a combination of glibenclamide 5 mg, metformin 500 mg, and acarbose 100 mg (19.5%). Almost all patients took their medications in the morning before meals (92.6%). The average weight gain was 4.6 kg, with the glibenclamide and metformin combination resulting in a 17% incidence. Conclusion: T2DM patients who use sulfonylureas generally gain weight and exhibit specific traits, including being middle-aged, female, and diabetic for multiple years. The most commonly used sulfonylureas are glimepiride for monotherapy and glibenclamide for combination therapy with metformin and acarbose. Future research is required to understand weight gain in T2DM patients treated with sulfonylureas more comprehensively. Highlights: 1. This study investigated weight changes in type 2 diabetes mellitus (T2DM) patients receiving sulfonylureas, with a special focus on the emergence of weight gain as a new problem in T2DM management. 2. The importance of this study pertains to its findings regarding weight gain in T2DM patients treated with sulfonylureas, offering additional data that aids in preventing adverse effects of the medications.